THE IMPLEMENTATION OF MERDEKA CURRICULUM IN ISLAMIC EDUCATION LEARNING AT SMK MUHAMMADIYAH LUMAJANG - Yunita, Laili; Widodo, Hendro (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
SMK Muhammadiyah Lumajang is an excellent vocational school that implements the Merdeka Curriculum for all subjects, including Islamic Religious Education learning. The implementation process of the Merdeka Curriculum runs swiftly, hence demanding educators to master and adapt to the Merdeka Curriculum. This study aims to examine the process of implementing the Merdeka Curriculum in Islamic Religious Education (PAI) learning, starting from the planning, implementation, and assessment stages. This research uses a qualitative field study approach, with data collection techniques consisting of observation, interviews, and documentation. The research subjects are the curriculum department vice principal, PAI teachers, and students. The data analysis techniques employed in this study include data reduction, data presentation, and conclusion drawing. The research findings indicate that the implementation of the Merdeka Curriculum in PAI learning has been realized, including 1) the planning stage that starts from the management of the school principal and curriculum vice principal in applying the Merdeka Curriculum 2) The implementation stage involves the teacher's preparation of the Annual Teaching Plan (ATP) and teaching modules in accordance with the learning outcomes set by the Ministry of Education and Culture. Furthermore, the assessment stage of PAI teachers involves the use of summative, formative, and Project-Based Learning (PBL) assessments.